Carry on classifying! The Moys reclassification project at the Bodleian Law Library - Garner, H (Cambridge University Press, 2018)
This article, written by Helen Garner, reviews the progress of the Moys Reclassification Project at the Bodleian Law Library and covers the issues relating to the lessons learnt and the benefits of changing to a different classification scheme. The Bodleian Law Library started work on the Moys Reclassification Project in 2006 and work is still on-going to complete the project.